Tasks Schedule Analysis in RTAI/Linux-GPL - Aciti, Claudio (2009)
Preemptive real-time operating systems allow the kernel to stop a running task to execute other task with higher priority. The tasks compete for the resources producing anomalies such as starvation, dead- lock and priority inversion that can reduce the perceived performance of the system. The scheduler is in charge of the synchronization when priorities are considered and of avoiding these anomalies to occur. Among the FOSS1 community, the RTAI2 real-time extension for the Linux kernel is one of the most applied and with major projection within the automatic control area. To synchronize priority tasks, RTAI has implemented the Priority Ceiling and the Priority Inheritance mechanisms. The main goal of this work is analyze the functioning of these mechanisms for di erent situations, in RTAI/Linux-GPL.